Formal market access barriers in small-scale broiler farming at Kromhoek Village, Blourberg Local Municipality, Limpopo Province: Formal market participation - Sekepe, Mahlatse Alfred; Belete, Abenet; Mokhaukhau, Jenny; Nengovhela, Rudzani (Indonesian Journal of Agricultural Research, 2025)
Poultry production is integral to the livelihoods of small-scale broiler chicken farmers in South Africa, serving as a potential source of income and food security. However, these farmers face challenges in accessing lucrative markets, limiting their economic potential. This study explored the factors influencing access to formal markets and analyzed the barriers hindering small-scale broiler farmers. A sample of 50 small-scale broiler farmers were interviewed, and a multivariate logistic model was used to analyze the data. The findings showed that trading on local and informal markets, the use of traditional production methods, limited marketing skills, the lack of extension services, and low revenue are barriers to formal market access for small-scale broiler farmers. In addition, the level of education, employment status, and distance to the market were the factors that hindered the market access of small-scale broiler farmers in the study area. Thus, easing market access barriers is key to tapping the economic potential of small-scale broiler chicken production and supporting sustainable growth in rural communities.